Evaluación de la calidad fisicoquímica de enalapril maleato 10 mg tabletas en el Centro Nacional de Control de Calidad del Instituto Nacional de Salud - Geronimo Boñón, José Alberto (2017)
The present report describes the trials performed on enalapril maleate 10 mg tablets to determine the physicochemical quality according to the United States Pharmacopoeia (USP) 39 and laboratory protocol of origin analysis. The tests were carried out in the physicochemical laboratory of the National Center of Quality Control of the National Institute of Health. The analyzes were made of the physical types which was according to the analytical technique of the manufacturer, the weight reached the result obtained with (99 ± 0,11) mg which meets the specifications according to British Pharmacopoeia, The chromatographic parameters of USP 39, content where it was determined that the tables analyzed contain 10.2 mg / Tab which is within the acceptance limits of USP 39 and lastly the dissolution where it was determined that none of the 6 tables Analyzed was less than the 80 (Q) minimum accepted by USP 39; With this you can conclude that this product meets the requirements of quality and fit for consumption